2018
DOI: 10.3389/fncel.2018.00147
|View full text |Cite|
|
Sign up to set email alerts
|

New Tools for Epilepsy Therapy

Abstract: One third of the epilepsies are refractory to conventional antiepileptic drugs (AEDs) and, therefore, identification of new therapies is highly needed. Here, we briefly describe two approaches, direct cell grafting and gene therapy, that may represent alternatives to conventional drugs for the treatment of focal epilepsies. In addition, we discuss more in detail some new tools, cell based-biodelivery systems (encapsulated cell biodelivery (ECB) devices) and new generation gene therapy vectors, which may help i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 53 publications
0
3
0
1
Order By: Relevance
“…Uma opção de terapêutica que é considerada eficaz para o tratamento da epilepsia refratária a medicamentos é justamente a cirurgia cerebral de ressecção. Sobretudo, este procedimento só deve ser considerado para epilepsias focais, por ser complexo e caro e muitas vezes é dificultado por obstáculos, como por exemplo: a proximidade de áreas cerebrais eloquentes, que impedem sua aplicação a muitos pacientes que podem se beneficiar dele (FALCICCHIA et al, 2018).…”
Section: Tratamento Cirúrgicounclassified
“…Uma opção de terapêutica que é considerada eficaz para o tratamento da epilepsia refratária a medicamentos é justamente a cirurgia cerebral de ressecção. Sobretudo, este procedimento só deve ser considerado para epilepsias focais, por ser complexo e caro e muitas vezes é dificultado por obstáculos, como por exemplo: a proximidade de áreas cerebrais eloquentes, que impedem sua aplicação a muitos pacientes que podem se beneficiar dele (FALCICCHIA et al, 2018).…”
Section: Tratamento Cirúrgicounclassified
“…Epilepsy is a neurological disorder characterized by the existence of seizures that occur because of abnormal excessive or synchronous neuronal activity in the brain, which can result from an insult, with unknown, focal, or generalized onset. [119][120][121] The anticonvulsive properties of adenosine are mainly mediated by A 1 Rs, with a decrease in A 1 Rs observed in the regions where seizures are generated. 119,122,123 Of interest, Ilie et al showed that endogenous adenosine was able to attenuate GABAergic signaling during epileptiform activity through the action of A 1 Rs on K + channels.…”
Section: Epilepsymentioning
confidence: 99%
“…Epilepsy, a common neurologic disease, affects a considerable number of people around the world (1). Anti-epileptic drugs (AEDs) are the main type of treatment for most people with epilepsy (2).…”
Section: Introductionmentioning
confidence: 99%